The use of Nucleus® CI422 in a ski-slope high-frequency hearing loss and chronic external ear pathology: A case study. (November 2013) - Távora-Vieira, Dayse; Rodrigues, Stephen
Abstract : Objective and importance: This case report illustrates the ongoing extending criteria for cochlear implantation (CI). It reinforces the statement that patients who do not fulfill the standard criteria for CI should be carefully considered on an individual basis. Clinical presentation: The patient on this report presented with a ski-slope high-frequency hearing loss and chronic external ear canal infections. The latter precluded the consistent use of hearing aids with moulds. His speech discrimination in quiet and in noise was poor and his hearing loss was interfering with his ability to work. Intervention: After years of frustration, this patient decided to risk losing his low-frequency residual hearing and was implanted with the new Nucleus ® CI422 (Cochlear Ltd). Conclusion: Hearing preservation was achieved and he gained a remarkable improvement in his hearing performance. It is thought that his outcomes are the result of the combination of hearing presentation surgery, electrode design, and intensive auditory training.